2012
DOI: 10.1089/dia.2011.0172
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Preretinopathic Diabetes Subjects and Antioxidants

Abstract: Results of this preliminary study suggest that an oral treatment with AOs in PRD subjects may have a protective effect on retinal cells, as detected by ERG analysis, through the strengthening of the plasma AO barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…Vitamin E is shown to ameliorate retinal hemodynamic abnormalities in diabetic patients [98], and oral administration of α-lipoic acid with genistein and vitamins for 30 days is shown to improve ERG oscillatory potential in patients with proliferative diabetic retinopathy [99]. Antioxidant properties containing calcium dobesilate and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 25 pycnogenol reduce the progression of diabetic retinopathy [100,101].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Vitamin E is shown to ameliorate retinal hemodynamic abnormalities in diabetic patients [98], and oral administration of α-lipoic acid with genistein and vitamins for 30 days is shown to improve ERG oscillatory potential in patients with proliferative diabetic retinopathy [99]. Antioxidant properties containing calcium dobesilate and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 25 pycnogenol reduce the progression of diabetic retinopathy [100,101].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In humans, a clinical trial with ALA supplementation failed to demonstrate prevention of diabetic macular oedema [57]. However, another study including diabetic subjects who had not yet developed retinopathy and who received ALA in combination with other antioxidants showed improvements in electroretinogram [58].…”
Section: Mechanism Of Action In Other Diabetic Complicationsmentioning
confidence: 99%
“…L-carnitine, which facilitates the transport of long chain fatty acids into mitochondria, improves insulin sensitivity in insulin-resistant patients, suggesting a possible beneficial effect on the progression of diabetic retinopathy [55]. Recently, a preliminary human study suggested that α-lipoic acid treatment improved the electroretinogram results in patients with diabetic retinopathy [56]. However, the treatment period was only 4weeks so the study could not reveal long-term results.…”
Section: Discussionmentioning
confidence: 99%